Hubungan motivasi kerja, kepemimpinan islami, kompensasi, dan komitmen organisasi terhadap kepuasan kerja di DPU PR Kota Salatiga - Farikhah, Iftaqul; Rofiuddin, Mohammad (Journal of Management and Digital Business, 2023)
This study aims to determine the effect of work motivation, Islamic leadership, compensation, and organizational commitment on job satisfaction at DPU PR Salatiga City. Data collection in this study was carried out by distributing questionnaires to DPU PR Salatiga City employees. The sample used in this research was 47 respondents. Multiple linear regression was used to analyze the data. The study results showed that work motivation, Islamic leadership, and compensation partially affected job satisfaction at DPU PR Salatiga City. Organizational commitment did not significantly affect job satisfaction. These results explain that an organization's leadership is vital and positively affects employee job satisfaction. In addition, motivation and compensation are drivers to achieve maximum job satisfaction.